Visual Representation of Selected Malaysian Political Trolling on Social Media: Disclose the Ideology and Power - Md Zahril Nizam bin Md Yusoff, Muhamad Fadzllah bin Hj Zaini (Tanjung Malim, 2024)
Visual Representation of Selected Malaysian Political Trolling on Social Media: Disclose the Ideology and Power by Md Zahril Nizam bin Md Yusoff, Muhamad Fadzllah bin Hj Zaini